Mengukur Prioritas Pengembangan Desa Wisata Di Era Pariwisata Baru - Dewa Ayu Made Lily Dianasari; Ida Bagus Putra Negarayana; I Gede Gian Saputra; Dewa Ayu Nyoman Aridayanti (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
The study aims to analyze the priority of developing tourist villages during the new normal period in Petang District, Badung Regency Bali. The theory and concepts used to answer the problems in this research are the concept of tourism product components, the concept of a tourism village, the concept of new normal tourism. The research method used is qualitative research using Analytical Hierarchy Process (AHP). Sources of data in this study are primary data and secondary data obtained through the process of observation, interviews and focus group discussions. The results of this study indicate that the priority of developing a tourism village in Petang District in the new normal era is an ancillary aspect as the main development priority. Then, the order of priority aspects of development that can be done next is attraction, accessibility, amenity, available packages and activity. Related to ancillary as the main priority aspect, there are institutional sub-criteria as things that can be prioritized first compared to the development of additional services. Based on the analysis that has been carried out, the form of institutional development that will be implemented is by holding a collaboration between the Petang District Government and the tourism institutional where the assistance collaboration is carried out in stages starting with the establishment of a tourism management system. KEY WORDS: tourism village, priority development, tourism product, new tourism era.